2008
DOI: 10.1158/1535-7163.mct-08-0046
|View full text |Cite
|
Sign up to set email alerts
|

RANK ligand inhibition plus docetaxel improves survival and reduces tumor burden in a murine model of prostate cancer bone metastasis

Abstract: Tumor cells induce excessive osteoclastogenesis, mediating pathologic bone resorption and subsequent release of growth factors and calcium from bone matrix, resulting in a ''vicious cycle'' of bone breakdown and tumor proliferation. RANK ligand (RANKL) is an essential mediator of osteoclast formation, function, and survival. In metastatic prostate cancer models, RANKL inhibition directly prevents osteolysis via blockade of osteoclastogenesis and indirectly reduces progression of skeletal tumor burden by reduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 39 publications
(34 reference statements)
1
52
0
1
Order By: Relevance
“…There has been increasing attention assigned to the role of RANKL in regulating cell motility (Jones et al, 2006;Mori et al, 2007;Armstrong et al, 2008;Chen et al, 2010;Hsu et al, 2010;Sabbota et al, 2010) and metastasis (Jones et al, 2006;Miller et al, 2008;Canon et al, 2008;Tan et al, 2011), with a significant emphasis on prostate and breast cancer cell metastasis to bone. Nonetheless, the role of RANK signaling through a homotypic scenario in the context of normal cell motility has yet to be investigated.…”
Section: Activation Of Rank Increases Osteosarcoma Cell Motilitymentioning
confidence: 99%
“…There has been increasing attention assigned to the role of RANKL in regulating cell motility (Jones et al, 2006;Mori et al, 2007;Armstrong et al, 2008;Chen et al, 2010;Hsu et al, 2010;Sabbota et al, 2010) and metastasis (Jones et al, 2006;Miller et al, 2008;Canon et al, 2008;Tan et al, 2011), with a significant emphasis on prostate and breast cancer cell metastasis to bone. Nonetheless, the role of RANK signaling through a homotypic scenario in the context of normal cell motility has yet to be investigated.…”
Section: Activation Of Rank Increases Osteosarcoma Cell Motilitymentioning
confidence: 99%
“…12,[42][43][44][45] Models employing OPG as a treatment for established bone metastases have also been described, and while OPG has been shown to reduce skeletal tumor burden in this setting, complete elimination of bone metastases from treatment with OPG alone has not been reported. [44][45][46][47] This reflects the difficulty of treating such well-established tumors and is not surprising, given that the ability of OPG to reduce tumor burden in the bone is the product of its antiresorptive activity rather than direct cytotoxicity. 46 We suggest that the delivery of sOPG-Fc by a CRAd has the potential to augment the therapeutic efficacy due to the directly oncolytic effect of viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…When they used direct histological analysis of the skeletal tumor burden, they found that OPG-Fc and docetaxel reduced histologic tumor burden within the bone by 82% and 83%, respectively. 35 Combination of the treatments enhanced the antitumor effect to 97.5% reduction compared with the control group, upon histological analysis. Median survival time with either OPG-Fc or docetaxel monotherapy did not differ significantly, although the distribution of their effects did.…”
Section: Tumor Burden (Anticancer)mentioning
confidence: 95%
“…26 The tumors cells in bone-treated with 3.0 mg kg --1 OPG-Fc twice weekly demonstrated significantly higher rates of apoptosis compared with control treatment. 26 Miller et al 35 evaluated the therapeutic use of OPG-Fc compared with docetaxel, an antimitotic agent that prevents microtubule depolymerization. Male athymic nu/nu mice were challenged with PC3 prostate cancer cells, and then treated with docetaxel, OPG-Fc, or a combination treatment with both agents.…”
Section: Tumor Burden (Anticancer)mentioning
confidence: 99%
See 1 more Smart Citation